MODERNISASI PENDIDIKAN PESANTREN ASWAJA; PENGEMBANGAN KURIKULUM BERBASIS IDENTITAS DAN KONTINUITAS - Ramdlani, Afif; Ulya, Sa’diyatul; Hikam, Ainul (Universitas Islam Malang, 2024)
As a traditional Islamic educational institution, Islamic boarding schools are often identified as conservative, static and underdeveloped educational institutions. This kind of stereotype cannot be fully justified, because in reality, Islamic boarding schools continue to transform both institutionally, systems, curriculum, etc. Regarding the development of Islamic boarding school curricula, not many researchers and academics are concerned with this field of study. This research is a literature review based on several previous studies. The results of this research show several conclusions. First, as a traditional Islamic educational institution in Indonesia, Islamic boarding schools have demonstrated success in maintaining their existence amidst globalization. Second, the Islamic boarding school curriculum has several superior aspects, including; aspects of identity, continuity, independence and flexibility. However, the Islamic boarding school curriculum also has shortcomings, namely Kiai-centric and Alineasi (alienation). Third, the components that an Islamic boarding school education curriculum must have consist of; objectives, knowledge content and learning experiences, strategies and evaluation